Jual Beli Dropshipping oleh Kalangan Mahasiswa IAIN Surakarta Menurut Hukum Islam - Iksan, Daimul (IAIN Surakarta, 2018)
AbstractThe development of information technology affects a variety of human life, including in the case of buying and selling transactions. If in previous years, buying and selling is usually direct, face to face. The current era of buying and selling without face to face is increasingly high by humans through a website system or platform. The buying and selling system also has various types, one of which is the dropshipper system. Behind the diversity of strengths, in terms of Islamic law the system has a variety of opinions that arise. Therefore, in this study, the author examines how Islamic law reviews the sale and purchase of the dropshipping system, especially among Surakarta IAIN students who are the objects of this research. This research is a qualitative research with descriptive analytical method. The results of the research, the sale of dropshipping in the study of Islamic law raises opportunities for default and the potential for harm associated with ownership of goods and the potential for fraud, but there are solutions to make the sale and purchase of dropshipping in accordance with Islamic law, namely by using the samsarah agreement, time, or greeting agreement. Of the three contracts, dropshipping sale and purchase carried out by students of IAIN Surakarta is a sale and purchase that is in conformity with the salam agreement and may be done as long as it meets the terms and conditions of the greeting agreement.Keywords: Dropshipper, Islamic law